Photodegradation of selected pharmaceuticals using magnetic-carbon dot loaded on different TiO2 nanostructures - Moshoeu, Edna Dimakatso (Vaal University of Technology, 2020)
To replace the conventional wastewater treatment technology, photocatalysis has the best potential due to its utilization of visible light to photodegrade organic and inorganic contaminants. However, agglomeration of nanoparticles leads to serious decrease in photocatalytic performance when applied in slurry form, due to hindrance effect. TiO2 semiconductor photocatalyst mediated advanced oxidation process is referred to as one of the most efficient technologies to degrade organic pollutants in water. However, TiO2 semiconductor for water purification hinders large scale applicability due to poor activity under visible light and the recombination of photogenerated electron and hole pairs. The modification of TiO2 semiconductor photocatalyst with carbon dots (CDs) is of high importance due to low toxicity, aqueous stability, enhanced surface area, economic feasibility, good biocompatibility and chemical inertness of CDs. Herein, strategies are highlighted to improve the activity of TiO2 semiconductor photocatalyst by coupling it with CDs and Fe2O3. In this study, we study the morphological influence of TiO2 nanostructures on photocatalytic degradation of tetracycline hydrochloride present in industrial wastewater. TiO2 nanostructures, nanotubes, nanospheres and nanofibers were Synthesized using the hydrothermal technique. TiO2 nanotubes, nanofibers and nanospheres were prepared by the hydrothermal treatment of TiO2 nanoparticles with different NaOH concentrations (5, 10 and 12 N) at 120 and 140 ˚C; afterwards, HCl was added until it reached pH 2. Both the crystalline phase and coordination of the TiO2 nanotubes, nanofibers and nanospheres were composed principally. Likewise, the surface area, pore volume and pore size of the TiO2 nanotubes, nanofibers and nanospheres changed with the NaOH rinsing treatment. The photocatalytic activity for tetracycline degradation were strongly enhanced by the nanofibers and nanotubes in the basic and acid media, respectively, showing a relationship between their structure and the medium. TiO2 nanostructures and the composite material were characterized by scanning electron microscope\SEM), X-Ray Diffraction (XRD), transmission electron microscope (TEM) and Fourier transform infrared (FTIR). BET surface area analysis was carried out using nitrogen adsorption desorption curves. The results show that TiO2 morphology had great influence on photocatalytic degradation of tetracycline hydrochloride due to difference in specific surface area and pore volume of nanostructures. The photocatalytic degradation experiments were carried out for three hours under visible-LED light. TiO2 nanofibers show better degradation performance than nanotubes and nanospheres due to presence of large surface area for reaction, higher porosity with dispersion of active sites at different length scales of pores and presence of oxygen vacancies. Agricultural biomass pine bark serves as a carbon source and was doped into TiO2-nanofibers (TNF) to fabricate the composite material (CD-TNF). CD-TNF composite nanofibers were prepared via a facile hydrothermal method. This study revealed that the photocatalytic efficiency of tetracycline (TC) under visible light irradiation of the composite nanofiber is higher than that of pure TiO2-nanofiber. The anchored CDs can both enhance the light absorption and suppress photogenerated electron hole recombination which results in the enhancement of catalytic and antibacterial properties. The CDs can better capture and transfer photogenerated electrons through the Ti-O-C and Fe-O-C bonds. Moreover, CDs can improve the utilization of photogenerated electrons and the electrons in CDs are captured by O2 to produce O2•- radicals and the role of O2•- radicals in the photocatalytic process is significantly improved. A new efficient photocatalyst consisting of TiO2/CD/Fe2O3 composite material was Synthesized by the hydrothermal treatment and applied in the photodegradation of 5 mg/L tetracycline hydrochloride (TC) under visible-LED light. The CDs/TiO2/Fe2O3 composite showed enhanced photocatalytic performance for tetracycline photodegradation when compared with TiO2/CDs and pure TiO2 under the visible light irradiation. The mechanism of the improved photocatalytic activity over CDs/TiO2/Fe2O3 was also investigated. The influence of the interface formation between Fe2O3 and TiO2/CDs affects severely the charges separation efficiency and enhances the electron transfer to keep on the existence of Fe3+/Fe2+ moieties that take significant role in the reaction mechanism.
M.Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Photodegradation; TiO2 Semiconductor photocatalyst; Photodegrade organic and inorganic contaminants; Nanoparticles; Agglomeration; Magnetic-carbon Dot loaded; Hindrance effect; Morphological influence of TiO2 nanostructures; Photocatalytic degradation of tetracycline hydrochloride; Dissertations, Academic -- South Africa.; Nanostructured materials.; Water -- Purification.; Carbon -- Magnetic properties.